Casting a Wider Net on Ocean NETs - Cox, Emily; Boettcher, Miranda; Spence, Elspeth; Bellamy, Rob (Frontiers in Climate, 2021)
Societal issues involving policies and publics are generally understudied in research on ocean-based Negative Emission Technologies (NETs), yet will be crucial if novel techniques are ever to function at scale. Publics influence political mandates and market uptake, and are key to robust decision-making and responsible incentivisation. Discourses surrounding ocean NETs will also have fundamental effects on governance for the techniques, shaping how they are defined, who is assigned the authority to govern, and what instruments are deemed appropriate. This Perspective brings together key insights on the societal dimensions of ocean NETs, including public acceptability, policy assessment, governance and discourse. Ocean iron fertilisation is the only ocean NET on which there exists considerable social science research, and we show that much evidence points against its social desirability. This, together with considerable natural science uncertainties, leads us to question whether further research is actually necessary to rule out ocean iron fertilisation as an option. For other ocean NETs, there are considerable knowledge gaps, yet the available evidence suggests that the majority of ocean NETs may face a greater public acceptability challenge than terrestrial NETs. Ocean NETs also raise complex governance questions which go well beyond the remit of natural sciences and engineering. Using a conceptual exploration of the ways in which different types of discourse may shape emerging ocean NETs governance, we show that the very idea of ocean NETs is likely to set the stage for a whole new range of contested futures.